2013
DOI: 10.3174/ajnr.a3619
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging of Orbital Masses: Multi-Institutional Data Support a 2-ADC Threshold Model to Categorize Lesions as Benign, Malignant, or Indeterminate

Abstract: BACKGROUND AND PURPOSE DWI has been increasingly used to characterize orbital masses and provides quantitative information in the form of the ADC, but studies of DWI of orbital masses have shown a range of reported sensitivities, specificities, and optimal threshold ADC values for distinguishing benign from malignant lesions. Our goal was to determine the optimal use of DWI for imaging orbital masses through aggregation of data from multiple centers. MATERIALS AND METHODS Source data from 3 previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
114
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 26 publications
6
114
1
3
Order By: Relevance
“…It is important to note that previous studies mainly included other benign and malignant orbital neoplastic lesions rather than inflammatory orbital lesions. [9][10][11][12][13][14][15] Sepahdari et al 10 reported that an ADC of less than 1.0 ϫ 10 Ϫ3 mm 2 /s was optimal for predicting malignancy and Politi et al 11 indicated that a threshold of 0.775 ϫ 10 Ϫ3 mm 2 /s was optimal for predicting orbital lymphoma. Therefore, their reported optimal ADC may be unfit for differentiating orbital lymphoma from benign OLPDs because these ADC values are higher than the ADCs of the majority of benign OLPDs found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that previous studies mainly included other benign and malignant orbital neoplastic lesions rather than inflammatory orbital lesions. [9][10][11][12][13][14][15] Sepahdari et al 10 reported that an ADC of less than 1.0 ϫ 10 Ϫ3 mm 2 /s was optimal for predicting malignancy and Politi et al 11 indicated that a threshold of 0.775 ϫ 10 Ϫ3 mm 2 /s was optimal for predicting orbital lymphoma. Therefore, their reported optimal ADC may be unfit for differentiating orbital lymphoma from benign OLPDs because these ADC values are higher than the ADCs of the majority of benign OLPDs found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recently, some researchers have reported quantitative DWI with ADC measurements to be potentially useful for discriminating orbital lymphoma from other orbital tumors. [9][10][11][12][13][14][15] However, these studies in-cluded other neoplastic and nonneoplastic lesions such as cavernous hemangiomas, neurogenic tumors, and metastases, and the value of DWI for discrimination of lymphoma and OLPDs remains unclear. The purpose of this study was to assess the value of MR imaging including DWI and contrast-enhanced MR imaging for the discrimination of primary orbital lymphoma from benign OLPDs.…”
mentioning
confidence: 99%
“…In head and neck cancer single-modality MRI, DWI is often performed for tumor detection and characterization, to monitor treatment response, and for the differentiation of recurrence from post-radiation changes [11,29,30]. However, the quality of the DWI sequence can be severely distorted by susceptibility artifacts, particularly in the head and neck area due to dental implants, and has a relatively low specificity [29][30][31].…”
Section: General Aspectsmentioning
confidence: 99%
“…Lymphomas are isointense to muscle on T1-weighted images, with relatively low signal intensity (appearing as dark areas) on the T2-weighted sequence [8,12]. Lesions enhance moderately but homogeneously without a prolonged delay since they are directly supplied by the orbital vasculature; they also show diminished diffusion typical of cellular lesions [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Fat suppression enhances the clearer visualization of lesions on T1-weighted images after contrast injection. Dynamic contrast-enhanced MRI has been employed to separate benign from malignant lymphoproliferations [13,14]. This methodology is based on successive scans linked closely over time in order to trace the speed of perfusion and other characteristics.…”
Section: Discussionmentioning
confidence: 99%